Effect of IBA and NAA on the Rooting and Vegetative Growth of Hardwood Cuttings in Common Fig (Ficus carica L.) - Nale, Rutuja; Sharma, Gaurav; Pal, Ranjit; Patel, R. K.; Sharma, Shivali (International Journal of Bio-resource and Stress Management, 2024)
The present investigation was carried out at Horticultural Nursery of Rani Lakshmi Bai Central Agricultural University (RLBCAU), Jhansi during the year 2021 to study the effect of different levels of IBA and NAA on the rooting and vegetative growth of hard wood cutting in common fig. The experiment was laid out in Completely Randomized Design in eleven treatments with three replications. The treatments comprised of IBA (500, 1000, 1500, 2000, 2500 ppm) and NAA (500, 1000,1500, 2000, 2500 ppm) by quick dip method along with control. The result indicated that IBA (2500 ppm) was found to be best in terms of early sprouting (10.26 days), Sprouted cutting (88.84%), survival % (87.29), number of roots cutting-1(12.35 and 20.86), length of longest root cutting-1 (23.01 cm), length of shoot (12.37 cm and 26.19 cm ), shoot diameter (1.59 cm), number of shoot cutting-1 (1.73 and 2.06) , fresh weight of roots cutting-1 (12.72 g), dry weight of roots cutting-1 (4.75 g) fresh weight of shoot cutting-1 (32.73 g), dry weight of shoot cutting-1 (9.19 g), number of leaves (8.77 and 11.40), leaf size i.e. length and width (14.20 cm and 13.56 cm), fresh weight of plant biomass (45.46 g) and dry weight of plant biomass (13.94 g).